Selected GRIN2A mutations in melanoma cause oncogenic effects that can be modulated by extracellular glutamate. Issue 6 (December 2016) - D'mello, Stacey Ann N.; Joseph, Wayne R.; Green, Taryn N.; Leung, Euphemia Y.; During, Matthew J.; Finlay, Graeme J.; Baguley, Bruce C.; Kalev-Zylinska, Maggie L.
Graphical abstract: Highlights: Melanoma cell lines contain functional NMDARs. Consequences of GRIN2A mutations in melanoma are heterogeneous. Certain GRIN2A mutations in melanoma induce oncogenic effects through the NMDAR. Effects of GRIN2A mutations in melanoma can be modulated by extracellular glutamate. Abstract: GRIN2A mutations are frequent in melanoma tumours but their role in disease is not well understood. GRIN2A encodes a modulatory subunit of the N -methyl-d -aspartate receptor (NMDAR). We hypothesized that certain GRIN2A mutations increase NMDAR function and support melanoma growth through oncogenic effects. This hypothesis was tested using 19 low-passage melanoma cell lines, four of which carried novel missense mutations in GRIN2A that we previously reported. We examined NMDAR expression, function of a calcium ion (Ca 2+ ) channel and its contribution to cell growth using pharmacological modulators; findings were correlated with the presence or absence of GRIN2A mutations. We found that NMDAR expression was low in all melanoma cell lines, independent of GRIN2A mutations. In keeping with this, NMDAR-mediated Ca 2+ influx and its contribution to cell proliferation were weak in most cell lines. However, certain GRIN2A mutations and culture media with lower glutamate levels enhanced NMDAR effects on cell growth and invasion. The main finding was that G762E was associated with higher glutamate-mediated Ca 2+ influx and stronger NMDAR contribution to cell proliferation, compared with wild-type GRIN2A and other GRIN2A mutations. The pro-invasive phenotype of mutated cell lines was increased in culture medium containing less glutamate, implying environmental modulation of mutation effects. In conclusion, NMDAR ion channel function is low in cultured melanoma cells but supports cell proliferation and invasion. Selected GRIN2A mutations, such as G762E, are associated with oncogenic consequences that can be modulated by extracellular glutamate. Primary cultures may be better suited to determine the role of the NMDAR in melanoma in vivo .